A Posteriori Error Estimate of Optimal Control Problem of PDE with Integral Constraint for State (Journal of Computational Mathematics, 2009)
In this paper, we study adaptive finite element discretization schemes for an optimal control problem governed by elliptic PDE with an integral constraint for the state. We derive the equivalent a posteriori error estimator for the finite element approximation, which particularly suits adaptive multi-meshes to capture different singularities of the control and the state. Numerical examples are presented to demonstrate the efficiency of a posteriori error estimator and to confirm the theoretical results.
Keywords: State-constrained optimal control problem; Adaptive finite element method; A posteriori error estimate.